Solve "x^2 - 12x - 45 = 0" by completing the square

The equation is of the formx2+bx+c=0This means it can be rearranged to(x+(b/2))2=(b/2)2-cTaking the square root of both sides leaves us with x.
x2-12x-45=0(x-(12/2))2-(12/2)2-45 = 0(x-6)2-62-45 = 0(x-6)2 = 45 + 36(x-6)2 = 81x-6 = 9x= 6 + 9 = 15

Answered by Elsa J. Maths tutor

5838 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

How do you find the area of a semi circle with a radius of 7cm?


Prove that (4x–5)^2 – 5x(3x – 8) is positive for all values of x.


Solve the simultaneous equations: 4x+y=25 and x-3y=16


How do I convert the following, 0.089, into standard form?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences